DOCUMENTATION STUDY OF 18TH CENTURY KULA REGION - KARAVAR, Gonca; AKTÜRK, Dorukhan Fırat (EUROASIA JOURNAL OF SOCIAL SCIENCES & HUMANITIES, 2020)
Hand-knotted carpets have an important place as they are among the material products of our culture. Today, the problem of ensuring the continuity of these lost values and transferring them to the future is frequently encountered. Many valuable hand-woven carpets are nowadays either in museums or in commercial circulation. For this reason, it is very difficult to find carpets that are historical and documented. All kinds of information compiled about spoiled, quality-changed, destroyed, hand-woven carpets that need to be protected have a documentary value. Documentation study is a process that continues from beginning to end in conservation applications. The purpose of the documentation study is to create a regular archive of the cultural assets under protection and to ensure that the necessary measures are taken. In the documentation studies, it is thought that the selection of the regions that have not been studied much and rare samples will increase the importance of hand-knotted carpets, which are our historical heritage. So the main source of our study is 18th century Kula region “Sarı Sulu” carpet. Kula is one of the important hand-knotted carpet centers in Western Anatolia. Researchers interested in Turkish carpet art and history have made many researches on carpets of the Kula region over time. Considering that hand-made carpet production has almost completely stopped today, it is seen that the information in most sources is insufficient in terms of reproduction. With these thoughts, the 18th century Kula region “Sarı Sulu” carpet, whose documentation study was carried out, was intended to make an academic contribution, since it has not been documented much and is a collection part. The information in this study has been gathered under two main headings as "Carpet Identity Information and Location" and "Artistic Features of the Carpet and Restitution Study", as it should be in the documentation study that forms the basis of conservation practices, and in-situ observation and analysis and literature research methods were used in the study.